Constructing phase diagrams of block copolymers with A-block-(B-stat-C) architecture - Weidinger, Britta; Coelln, Nadine von; Yang, Guohui; Nirschl, Hermann; Wacker, Irene; Schröder, Rasmus R.; Tegeder, Petra; Blasco, Eva (Polymer chemistry, 2024)
Block copolymers (BCPs) are capable of self-organizing into precise nanoscale structures, generating interest across diverse fields such as drug delivery, catalysis, and lithography. Introducing new functionalities to BCPs through post-modification is a widely used approach. To further advance the design of functional BCPs, it is essential to understand how the incorporated functional groups affect their morphology. In this study, we focus on BCPs with an A-block-(B-statistical-C) architecture, where A is poly(styrene), B is poly(methyl methacrylate), and C is poly(2-hydroxyethyl methacrylate), which allows for the addition of photo-crosslinkable groups like methacrylates. In particular, we have synthesized a library of over twenty well-defined BCPs with different compositions and molecular weights using RAFT polymerization. Afterwards, we created a second library by introducing methacrylate groups through post-functionalization. The morphologies of these two sets of BCPs were carefully analyzed using small-angle X-ray scattering (SAXS), scanning electron microscopy (SEM), and infrared scanning near-field optical microscopy (IR-SNOM). By combining this data, we have built phase diagrams for both the original and functionalized copolymers and examined how post-functionalization affects their morphology. Our findings reveal that even small changes in the polymer composition significantly impact the morphological behavior.
Gesehen am 05.03.2025